(untitled) (Research, Society and Development, 2020)
This study aims to understand the gastrointestinal and nutritional symptomatological relationships and their possible relationships of people with autism spectrum disorder. The aim of this study was to conduct an integrative review on autism and gastrointestinal disorders in a comprehensive manner, analyzing diet and nutrition, and functional difference of the gastrointestinal tract in patients with ASD. For the selection of the sample, criteria were defined for articles indexed from 2010 to 2020, published in national and international journals, available in full in Portuguese and English. Data collection was carried out in the Virtual Health Library (VHL), LILACS, SCIELO, PubMed, and GOOGLE ACADÊMICO database, using the following descriptors "Autism", "Gastrointestinal Disorders", "Nutritional Disorder". The search resulted in 138 articles after using the inclusion and exclusion criteria, leaving 15 articles for analysis, interpretation and discussion. The results show that there is a relationship between food and gastrointestinal disorders, causing nutritional problems and making it difficult to take adequate measures in the time necessary for a better approach in dietary interventions. We conclude that an approach to change in relation to food in the diet of people with ASD would be important, in addition to considering the heterogeneity of the autistic population. There is insufficient scientific evidence in exploratory and review studies to prove that a restrictive diet improves symptoms of gastrointestinal disorders, microbiota functionalities and nutritional aspects in ASD.